2017
DOI: 10.1017/s1368980017003421
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal infant and young child feeding practices among internally displaced persons during conflict in eastern Ukraine

Abstract: ObjectiveTo determine current status, areas for improvement and effect of conflict on infant and young child feeding (IYCF) practices among internally displaced persons (IDP) in eastern Ukraine.DesignCross-sectional household survey, June 2015.SettingKharkiv, Dnipropetrovsk and Zaporizhia oblasts (Ukrainian administrative divisions) bordering conflict area in Ukraine.SubjectsRandomly selected IDP households with children aged <2 years registered with local non-governmental organizations. Questions based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 29 publications
2
32
1
6
Order By: Relevance
“…From our reading of the literature, Zakanj et al [66], Summers and Bilukha [54], and Guerrero-Serdan [32] are the only studies that touch on the relationship between war and breastfeeding. Zakanj et al, using descriptive statistics from survey data collected in Croatia, find that conflict is associated with a reduction in both the prevalence and duration of breastfeeding, and argue that this is most likely due to the distribution of infant food by international organizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our reading of the literature, Zakanj et al [66], Summers and Bilukha [54], and Guerrero-Serdan [32] are the only studies that touch on the relationship between war and breastfeeding. Zakanj et al, using descriptive statistics from survey data collected in Croatia, find that conflict is associated with a reduction in both the prevalence and duration of breastfeeding, and argue that this is most likely due to the distribution of infant food by international organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Zakanj et al, using descriptive statistics from survey data collected in Croatia, find that conflict is associated with a reduction in both the prevalence and duration of breastfeeding, and argue that this is most likely due to the distribution of infant food by international organizations. Summers and Bilukha [54], using a survey of internally displaced persons in the Ukraine, find that conflict-related stress is the most frequently reported reason for early breastfeeding termination. Guerrero-Serdan [32] briefly explores the effect of the 2003 Iraq war on breastfeeding, only insofar as it acts as a transmission channel to poor nutritional outcomes of children, which is the focus of that paper.…”
Section: Introductionmentioning
confidence: 99%
“…Bayi dan anak usia dini di pengungsian pasca konflik Uganda mayoritas sebagian ada yang mulai MPASI pada usia 3 atau 4 bulan (Nassanga et al, 2018). Hal serupa terjadi di pengungsian Ukraina bahwa hampir seperlima bayi berusia kurang dari 6 bulan menerima makanan berupa bubur bayi instan, puree buah atau sayuran instan, dan buah utuh (Summers & Bilukha, 2018). Selain itu, di pengungsian daerah kumuh Dhaka-Bangladesh disebutkan bahwa pengasuh makanan atau minuman manis sejak anak berusia kurang dari 6 bulan (Kabir & Maitrot, 2017).…”
Section: Usia Pengenalan Mpasiunclassified
“…Adherence to recommended infant and young child feeding (IYCF) practices has been identified as a key area that can help tackle undernutrition and ultimately improve child health [1]. In addition, Summers and Bilukha (2018) [2] reported that introducing complementary foods at 6 months of age is the third leading child health intervention in preventing child deaths. As a result of the evidence of the impact of appropriate feeding on child health, the WHO and UNICEF recommend early initiation of breast-feeding within the first hour of birth, exclusive breast-feeding for the first 6 months of life, continued breast-feeding until 2 years of age, and timely introduction of nutritious complementary foods at 6 months of age [3].…”
Section: Introductionmentioning
confidence: 99%